Martensite adaption through epitaxial nano transition layers in TiNiCu shape memory alloys. Issue 3 (1st June 2016) - Dankwort, Torben; Strobel, Julian; Chluba, Christoph; Ge, Wenwei; Duppel, Viola; Wuttig, Manfred; Quandt, Eckhard; Kienle, Lorenz
Abstract : The crystallographic origin of ultralow superelastic fatigue in NiTi‐based shape memory alloys is explored. Ti‐rich precipitates are coupled to austenite and martensite, and serve as epitaxial seeds during the repeated phase transformations. Abstract : Titanium‐rich TiNiCu shape memory thin films with ultralow fatigue have been analysed for their structural features by transmission electron microscopy. The stabilization of austenite (B2) and orthorhombic martensite (B19) variants epitaxially connected to Ti2 Cu‐type precipitates has been observed and found responsible for the supreme mechanical cycling capability of these compounds. Comprehensive ex situ and in situ cooling/heating experiments have demonstrated the presence of an austenitic nanoscale region in between B19 and Ti2 Cu, in which the structure shows a gradual transition from B19 to B2 which is then coupled to the Ti2 Cu precipitate. It is proposed that this residual and epitaxial austenite acts as a template for the temperature‐induced B2↔B19 phase transition and is also responsible for the high repeatability of the stress‐induced transformation. This scenario poses an antithesis to residual martensite found in common high‐fatigue shape memory alloys.